If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 + 5n = 11n Solving 42 + 5n = 11n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-11n' to each side of the equation. 42 + 5n + -11n = 11n + -11n Combine like terms: 5n + -11n = -6n 42 + -6n = 11n + -11n Combine like terms: 11n + -11n = 0 42 + -6n = 0 Add '-42' to each side of the equation. 42 + -42 + -6n = 0 + -42 Combine like terms: 42 + -42 = 0 0 + -6n = 0 + -42 -6n = 0 + -42 Combine like terms: 0 + -42 = -42 -6n = -42 Divide each side by '-6'. n = 7 Simplifying n = 7
| 2.2+3.2=42 | | t^4-37t^2+36= | | 36+5x=9x | | k+13=14k | | 100-9x=199 | | 6x+8=7x | | 2y+3=5y | | 16a^3b^4+40a^2b^5+8ab^3= | | -60+-30= | | 94-2x=54 | | 9x^3y+33x^2y^2+30xy^3= | | 5(x+1)=3x-2(x+1) | | 3(x+2)+2x=6 | | 2x^4y-3x^3y-20x^2y= | | -x^2-x+3=0 | | -24x^2-15=39x-2 | | 90-4x=6 | | 3x^3-x^2y+12x-4y= | | 1x-1+1-1+1-1+1-1+1-1+1=70000 | | 34x+3454=2000 | | 5x^2+20xy-60y^2= | | 5p+7=3p+21 | | 4x^3y-49xy^3= | | 2x^2-2=20 | | 3n^2-17n+24= | | 3(2z+1)=2(2x+2)+x | | 10(2x-5)-6=5 | | 7(x+3)=4(x+12) | | 10-x^2=-26 | | 4x-7=113-11x | | 7x+4=2x+39 | | 3(n+3)=22 |